PENGARUH MUSIK INSTRUMENTAL TERHADAP KUALITAS HIDUP PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - Tiarnida Nababan (Universitas Prima Indonesia, 2021)
Chronic renal failure or late-stage renal disease is a progressive and irreversible disorder of renal function (the body fails in maintaining metabolism and balance of fluids and electrolytes), thereby causing uremia (retention of urea and other nitrogen waste in the blood). Treatment of kidney failure disease can be done by pharmacological and non-pharmacological means. Non-pharmacological treatment can be in the form of the provision of instrumental music. This study aims to find out the influence of instrumental music on quality of life in chronic kidney failure patients undergoing hemodialysis at the Royal Prima Hospital Medan. This type of research is pre-experimental research with a one-group pre-post-test design with the provision of instrumental music for 20 minutes. The population is 66 people and sampled as many as 20 people with accidental sampling techniques. The analysis used in using Wilcoxon test. Based on the calculation of the Wilcoxon signed-rank test, obtained Z= - 3,938 with (p=0.000) < 0.05, so it can be concluded that there is an instrumental music influence on the quality of life in chronic renal failure patients undergoing hemodialysis at Royal Prima Medan Hospital in 2018. It is recommended that instrumental music can be applied as an alternative therapy to improve the quality of life.